Review of Psorodonotus Specularis Group (Orthoptera, Tettigoniidae, Tettigoniinae): two new species from North-east Anatolia - Kaya, Sarp; Chobanov, Dragan; Çiplak, Battal (Zootaxa, 2014)
The Anatolio-Caucasio-Balkan genus Psorodonotus (Orthoptera, Tettigoniidae) presently includes 13 species belonging to three species groups. In the present study we review the Specularis group and describe two new species—P. rize Kaya & Ciplak sp. n. and P. giresun Kaya & Ciplak sp. n.. Data obtained of 21 different populations from the North-eastern Anatolia and the Caucasus are used for descriptive and analytical purposes. Morphology of this group has been studied both qualitatively and quantitatively using linear metric data of the hind femur and geometric data of male and female pronotum, male cerci and ovipositor. Male calling songs are described and statistically analysed. Qualitative and/or quantitative morphology and male calling song suggested seven taxonomic units: P. specularis specularis, P. specularis inermis, P. inflatus, P. davisi, P. soganli, P. rize sp. n., P. giresun sp. n.. Our results suggest closest relationships of P. rize sp. n. with P. davisi and of P. giresun sp. n. with P. soganli.